Studi Eksperimen Penambahan Tailing Pada Campuran Mortar Sebagai Substitusi Parsial Semen Untuk Dinding Panel - Kurniaty, D.R. (Civil Engineering Department, Tadulako University, 2022)
Poboya is located in East Palu District, Palu City, Central Sulawesi. This village is now an area that has become a traditional gold mining activity. The end result of the mining process in the form of these deposits becomes waste which is commonly referred to as tailing. This waste contains a lot of carbon and no one has utilized it. This study was conducted to determine the optimum percent value of adding tailing to the mortar mixture so that it can affect the compressive strength of the mortar. This research uses experimental methods and literature studies. The location of the research was carried out at the Laboratory of Structures and Building Materials, Faculty of Engineering, Tadulako University. The variations used in the use of gold mine waste (tailing) as partial cement substitution are 50% and 75% by weight of cement. Tailings will replace some of the cement in a mortar mix made of sand, cement and water. The test to be carried out is the compressive strength of the mortar at the age of 7 and 28 days. Mortar test object made measuring 5 x 5 x 5 cm. The results obtained showed that 50% tailings had a higher compressive strength of 156 kg/cm2 than mortar using 75% tailing only had a compressive strength of 21.33 kg/cm2 at the age of the specimen 28 days. Mortar is used for the manufacture of wall panels with ferrocement technology.